Blanca Rodríguez López, Nuria Sánchez Madrid y Adriana Zaharijević (Eds.). (2021). Rethinking Vulnerability and Exclusion. Historical and Critical Essays. Palgrave Macmillan. 232 pp. - Liedo, Belén (Las Torres de Lucca. International Journal of Political Philosophy, 2022)
Blanca Rodríguez López, Nuria Sánchez Madrid and Adriana Zaharijević (eds.), 2021, Rethinking Vulnerability and Exclusion. Historical and Critical Essays, Palgrave Macmillan, 232 pp.